Corrosion-resistant steel-cored aluminum strand and method for manufacturing the same
Patent Information
- Application Number
- CN202611391159.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-09
AI Technical Summary
然而,目前的方法仍存在局限性:镀层在长期服役中因微动磨损、机械划伤或腐蚀介质渗透而逐渐失效后,铝与钢的直接接触难以根本避免,界面电偶腐蚀仍持续发生;而牺牲导电率换取强度提升的做法,在大容量输电场景下会加剧线路损耗,削弱了钢芯铝绞线的节能优势
1. 本发明在防腐涂料中添加偶联剂改性的高熵硼化物作为防腐填料,进而有效提高铝绞线的耐腐蚀性和耐磨性。高熵硼化物具有高硬度和高化学稳定性,作为填料能够有效提升线材的耐磨性能和防腐性能,但直接与树脂混合会存在表面能高、易团聚等问题,分散性和相容性均会受到影响。因此,本发明先对高熵硼化物进行酸处理,暴露其表面的活性位点,再利用偶联剂进行改性,使硼化物分散性得到改善;然后利用偶联剂中的氨基基团与巯基乙酸和三氟丙酸中的羧基反应,使巯基和三氟甲基基团共同接枝于硼化物表面;其中,巯基能够与环氧树脂反应形成交联网络结构,提升高熵硼化物与有机基体的相容性,而三氟甲基则具有强稳定性,二者协同构建有机-无机复合网络结构,作为铝绞线的防腐填料,能够进一步提升铝绞线的耐腐蚀性能。
Smart Images

Figure CN122889527A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum stranded wire technology, specifically relating to a corrosion-resistant steel-cored aluminum stranded wire and its preparation method. Background Technology
[0002] Steel-cored aluminum stranded wire, with its structural design advantage of "steel core bearing mechanical load and hard aluminum wire transmitting current", has been widely used in long-distance, large-capacity power transmission projects, effectively achieving the unity of long-span erection and low line loss.
[0003] However, as the power grid operating environment becomes increasingly complex, its application bottlenecks are becoming more apparent. On the one hand, electrochemical corrosion easily occurs at the interface between the hard aluminum wire and the steel core. Although the steel core is not designed to conduct electricity, the conductor experiences fretting wear due to dynamic loads such as wind vibration and galloping during long-term operation. Combined with unavoidable local contact during manufacturing and construction, this results in direct contact between the aluminum and steel. Due to the significant potential difference between the two, galvanic corrosion forms in humid or polluted environments, leading to localized corrosion and even strand breakage of the aluminum wire, seriously threatening line safety and service life. On the other hand, there is an inverted "conductivity-strength" relationship in the materials used. High conductivity requires the use of high-purity aluminum, but its tensile strength is insufficient; while using high-strength aluminum alloys can improve load-bearing capacity, it inevitably reduces conductivity. It is difficult to achieve optimal synergy between the two in a single material system.
[0004] To address the aforementioned issues, existing research primarily focuses on surface protection and material optimization. For example, the use of galvanized steel cores, galvanized aluminum-magnesium steel cores, or aluminum-clad steel cores has mitigated interfacial corrosion to some extent. Simultaneously, the introduction of high-strength aluminum alloys or heat treatment strengthening attempts to find a compromise between conductivity and strength. However, current methods still have limitations: after the coating gradually fails due to fretting wear, mechanical scratches, or corrosive media penetration during long-term service, direct contact between aluminum and steel is difficult to completely avoid, and interfacial galvanic corrosion continues to occur. Furthermore, sacrificing conductivity for increased strength can exacerbate line losses in high-capacity transmission scenarios, weakening the energy-saving advantages of steel-cored aluminum stranded wire.
[0005] Therefore, existing improvement methods are insufficient to simultaneously meet the comprehensive application requirements of high conductivity, high strength, and corrosion resistance. There is an urgent need to develop a steel-cored aluminum stranded wire that can achieve all of these properties. Summary of the Invention
[0006] The purpose of this invention is to provide a corrosion-resistant steel-cored aluminum stranded wire and its preparation method, which has both high conductivity and tensile strength as well as good corrosion resistance.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing steel-cored aluminum stranded wire, comprising the following steps: (1) Aluminum alloy and silver-plated graphene are mixed evenly, melted and then refined and dehydrogenated, and then continuously cast and extruded and drawn to obtain hard aluminum wire. (2) Spray anti-corrosion coating on the surface of the steel core and dry it to obtain a pretreated steel core; strand hard aluminum wire into the outer layer of the pretreated steel core, immerse it in alkaline solution, clean it, dry it, spray anti-corrosion coating again and dry it to obtain steel core aluminum stranded wire. The anti-corrosion coating is composed of the following components by weight percentage: 15-24 wt% anti-corrosion filler, 4-8 wt% butyl acetate, 22-27 wt% polyvinyl fluoride resin, and the balance being epoxy resin.
[0008] Furthermore, the anti-corrosion filler is prepared by the following process: (a) A mixture of metal oxide, boron carbide and graphite was calcined in an inert gas atmosphere to obtain a high-entropy boride; (b) The high-entropy boride was ultrasonically treated in an acid solution, and then heated and stirred with a silane coupling agent in ethanol to obtain the modified high-entropy boride; (c) Modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid and dehydrating agent are added to toluene and stirred under heating conditions to obtain corrosion-resistant filler.
[0009] Further, the metal oxide in step (a) is composed of any five raw materials selected from HfO2, ZrO2, Ta2O5, V2O5, Nb2O5, TiO2, Cr2O3, MoO3, WO3, or CeO2 in an equimolar ratio; the molar ratio of the metal oxide, boron carbide, and graphite is 1:(0.7-1.1):(0.3-0.5); the calcination temperature is 1500-1600 ℃, and the time is 2-4 h.
[0010] Further, the ultrasonic treatment in step (b) involves soaking in a 3-5 wt% nitric acid solution for 0.5-1.5 h; the silane coupling agent is KH550; the ratio of the high-entropy boride, silane coupling agent, and ethanol is 100 g: (10-15) g: (300-400) mL; and the heating and stirring temperature is 50-70 ℃ for 1-2 h.
[0011] Further, the dehydrating agent in step (c) is propylphosphonic anhydride; the ratio of the modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, dehydrating agent and toluene is 100 g: (2-3) g: (3-4.5) g: (10-15) g: (200-250) mL; the heating temperature is 40-50 ℃, and the stirring reaction time is 2-5 h.
[0012] Further, the silver-plated graphene described in step (1) is prepared by the following method: Pretreated graphene is dispersed in a chemical plating solution, sonicated for 20-40 min, filtered, and washed to obtain silver-plated graphene. The chemical plating solution is composed of the following raw materials by mass percentage: 2wt% silver nitrate, 2-3wt% glucose, 6-10wt% potassium sodium tartrate, 4-5wt% ethanol, and the balance is water.
[0013] Furthermore, the pretreated graphene is obtained by heating and soaking graphene in a sodium hydroxide solution; the ratio of the pretreated graphene to the chemical plating solution is 1 g: (125-250) mL.
[0014] Furthermore, the ratio of graphene to sodium hydroxide solution is 1 g:(1-1.2) L; the concentration of sodium hydroxide solution is 0.5-1 mol / L; the heating and soaking temperature is 70-80 ℃, and the time is 1-2 h.
[0015] Further, in step (1), the mass ratio of silver-plated graphene to aluminum alloy is (0.15-0.3):(99.85-99.7); the temperature during continuous casting and extrusion is 680-690 ℃.
[0016] Further, the aluminum alloy described in step (1) is composed of the following components by mass percentage: Fe 0.11-0.21 wt%, Si 0.15-0.24 wt%, B 0.06-0.18 wt%, Cu 0.25-0.32 wt%, La 0.04-0.08 wt%, Ce 0.06-0.12 wt%, with the balance being Al.
[0017] A second aspect of the present invention provides a steel-cored aluminum stranded wire prepared by the preparation method described in the first aspect above.
[0018] The beneficial technical effects of this invention are as follows: 1. This invention adds a coupling agent-modified high-entropy borides to an anti-corrosion coating as an anti-corrosion filler, thereby effectively improving the corrosion resistance and wear resistance of aluminum stranded wire. High-entropy borides possess high hardness and high chemical stability, and as a filler, they can effectively improve the wear resistance and corrosion resistance of wire. However, direct mixing with resin can lead to problems such as high surface energy and easy agglomeration, affecting dispersibility and compatibility. Therefore, this invention first acid-treats the high-entropy borides to expose their surface active sites, and then modifies them using a coupling agent to improve the dispersibility of the borides. Then, the amino groups in the coupling agent react with the carboxyl groups in mercaptoacetic acid and trifluoropropionic acid, causing thiol and trifluoromethyl groups to be grafted onto the surface of the borides. Among them, the thiol groups can react with epoxy resin to form a cross-linked network structure, improving the compatibility of high-entropy borides with the organic matrix, while the trifluoromethyl groups have strong stability. The two work together to construct an organic-inorganic composite network structure, which, as an anti-corrosion filler for aluminum stranded wire, can further improve the corrosion resistance of the aluminum stranded wire.
[0019] 2. This invention adds silver-plated graphene to hard aluminum wire, thereby effectively improving the mechanical and electrical properties of the aluminum stranded wire. Silver-plated graphene combines the high conductivity of both silver and graphene, forming a good conductive path in the alloy matrix, thus improving the conductivity of the hard aluminum wire. Simultaneously, graphene acts as a reinforcing phase, refining grains and hindering dislocation movement in the alloy matrix, thus improving the mechanical properties of the hard aluminum wire. Furthermore, the dispersion and wettability of graphene in the matrix are improved after silver plating, further enhancing the strengthening effect. Attached Figure Description
[0020] Figure 1 A scanning electron microscope image of the anti-corrosion filler prepared in Example 1 of this invention; Figure 2 The image is a scanning electron microscope (SEM) image of the silver-plated graphene prepared in Example 6 of this invention. Detailed Implementation
[0021] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention. Specific conditions not specified in the embodiments are performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used are conventional products obtained through commercial channels.
[0022] The aluminum alloy composition in the following examples and comparative examples is: Fe 0.16 wt%, Si 0.19 wt%, B 0.12 wt%, Cu 0.3 wt%, La 0.06 wt%, Ce 0.09 wt%, with the balance being Al.
[0023] (a) Preparation example Preparation Example 1 Preparation Example 1 provides an anti-corrosion coating, which is prepared by the following process: (a) TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite were ball-milled and mixed evenly according to the molar ratio of TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite of 1:1:1:1:1:4:2, and calcined at 1500 °C for 3 h under an argon atmosphere to obtain high-entropy borides; (b) According to the ratio of high-entropy boride, nitric acid solution, silane coupling agent KH550 and ethanol, 100 g: 240 mL: 12 g: 320 mL, the high-entropy boride was added to 4 wt% nitric acid solution and sonicated for 1 h. After filtration, washing and drying, it was added to ethanol along with silane coupling agent KH550 and stirred at 60 ℃ for 1 h. After filtration, washing and drying, the modified high-entropy boride was obtained. (c) According to the ratio of modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, propylphosphonic anhydride, and toluene (100 g: 2 g: 4 g: 12 g: 220 mL), the modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, and propylphosphonic anhydride were added to toluene and stirred at 45 °C for 3 h. After filtration, washing, and drying, the corrosion-resistant filler was obtained. The scanning electron microscope image of the corrosion-resistant filler is shown below. Figure 1 As shown; (d) Weigh the raw materials according to 20 wt% anti-corrosion filler, 6 wt% butyl acetate, 25 wt% polyvinyl fluoride resin and 49 wt% epoxy resin, mix the above anti-corrosion filler, butyl acetate, polyvinyl fluoride resin and epoxy resin evenly to obtain anti-corrosion coating.
[0024] Preparation Example 2 Preparation Example 2 provides an anti-corrosion coating, which is prepared by the following process: (a) TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite were ball-milled and mixed evenly according to the molar ratio of TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite of 1:1:1:1:1:3.5:1.5, and calcined at 1500 °C for 2 h under an argon atmosphere to obtain high-entropy borides; (b) According to the ratio of high-entropy boride, nitric acid solution, silane coupling agent KH550 and ethanol, 100 g: 300 mL: 10 g: 300 mL, the high-entropy boride was added to 3 wt% nitric acid solution and sonicated for 0.5 h. After filtration, washing and drying, it was added to ethanol along with silane coupling agent KH550 and stirred at 50 ℃ for 1 h. After filtration, washing and drying, the modified high-entropy boride was obtained. (c) According to the ratio of modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, propylphosphonic anhydride and toluene, 100 g: 2 g: 3 g: 10 g: 200 mL, the modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid and propylphosphonic anhydride were added to toluene and stirred at 40 °C for 2 h. After filtration, washing and drying, the anticorrosive filler was obtained. (d) Weigh the raw materials according to 15 wt% anti-corrosion filler, 4 wt% butyl acetate, 27 wt% polyvinyl fluoride resin and 54 wt% epoxy resin, and mix the above anti-corrosion filler, butyl acetate, polyvinyl fluoride resin and epoxy resin evenly to obtain anti-corrosion coating.
[0025] Preparation Example 3 Preparation Example 3 provides an anti-corrosion coating, which is prepared by the following process: (a) TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite were ball-milled and mixed evenly according to the molar ratio of TiO2, Cr2O3, ZrO2, Nb2O5, CeO2, boron carbide and graphite of 1:1:1:1:1:5.5:2.5, and calcined at 1600 °C for 4 h under an argon atmosphere to obtain high-entropy borides; (b) According to the ratio of high-entropy boride, nitric acid solution, silane coupling agent KH550 and ethanol, 100 g: 300 mL: 15 g: 400 mL, the high-entropy boride was added to 5 wt% nitric acid solution and sonicated for 1.5 h. After filtration, washing and drying, it was added to ethanol along with silane coupling agent KH550 and stirred at 70 ℃ for 2 h. After filtration, washing and drying, the modified high-entropy boride was obtained. (c) According to the ratio of modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, propylphosphonic anhydride and toluene, 100 g: 3 g: 4.5 g: 15 g: 250 mL, the modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid and propylphosphonic anhydride were added to toluene and stirred at 50 °C for 5 h. After filtration, washing and drying, the anticorrosive filler was obtained. (d) Weigh the raw materials according to 24 wt% anti-corrosion filler, 8 wt% butyl acetate, 22 wt% polyvinyl fluoride resin and 46 wt% epoxy resin, and mix the above anti-corrosion filler, butyl acetate, polyvinyl fluoride resin and epoxy resin evenly to obtain anti-corrosion coating.
[0026] Preparation Example 4 This preparation example is basically the same as Preparation Example 1, except that the anti-corrosion filler in step (d) is omitted, and the amount of epoxy resin is increased to 69 wt%.
[0027] Preparation Example 5 This preparation example is basically the same as Preparation Example 1, except that the anti-corrosion filler in step (d) is replaced with an equal amount of high-entropy boride.
[0028] Preparation Example 6 Preparation Example 6 provides a silver-plated graphene, prepared by the following process: A chemical plating solution was prepared according to the following formula: 2 wt% silver nitrate, 2 wt% glucose, 8 wt% potassium sodium tartrate, 4 wt% ethanol, and 84 wt% water. Graphene was added to a 0.8 mol / L sodium hydroxide solution at a ratio of 1 g:1 L and ultrasonically dispersed at 70 °C for 2 h. After filtration and washing, pretreated graphene was obtained. Then, the pretreated graphene was added to the chemical plating solution at a ratio of 1 g:175 mL and ultrasonically dispersed for 30 min. After filtration, washing, and drying, silver-plated graphene was obtained. The scanning electron microscope image of the silver-plated graphene is shown below. Figure 2 As shown.
[0029] Preparation Example 7 Preparation Example 7 provides a silver-plated graphene, which is prepared by the following process: A chemical plating solution was prepared according to 2wt% silver nitrate, 2wt% glucose, 6wt% potassium sodium tartrate, 4wt% ethanol, and 86wt% water, and set aside. Graphene was added to a 0.5 mol / L sodium hydroxide solution at a ratio of 1 g:1 L and ultrasonically dispersed at 75 °C for 1 h. After filtration and washing, pretreated graphene was obtained. Then, pretreated graphene was added to the chemical plating solution at a ratio of 1 g:250 mL and ultrasonically dispersed for 20 min. After filtration, washing, and drying, silver-plated graphene was obtained.
[0030] Preparation Example 8 Preparation Example 8 provides a silver-plated graphene, prepared by the following process: Prepare a chemical plating solution using 2wt% silver nitrate, 3wt% glucose, 10wt% potassium sodium tartrate, 5wt% ethanol, and 80wt% water. Add graphene to a 1 mol / L sodium hydroxide solution at a ratio of 1 g:1.2 L and ultrasonically disperse at 80 °C for 1 h. Filter and wash to obtain pretreated graphene. Then, add the pretreated graphene to the chemical plating solution at a ratio of 1 g:125 mL and ultrasonically disperse for 40 min. Filter, wash, and dry to obtain silver-plated graphene.
[0031] (II) Implementation Examples Example 1 Example 1 provides a method for preparing corrosion-resistant steel-cored aluminum stranded wire, comprising the following steps: (1) Weigh the raw materials according to 0.2 wt% silver-plated graphene and 99.8 wt% aluminum alloy, ball mill and mix the aluminum alloy with the silver-plated graphene of Preparation Example 6, heat to 710-720 ℃ to melt, then refine and dehydrogenate, continuously cast and extrude at 680 ℃ to obtain round aluminum rods, and then draw to obtain hard aluminum wires. (2) After the steel core is degreased, washed and dried, and sandblasted to remove rust, the anti-corrosion coating of Preparation Example 1 is sprayed on the surface of the steel core with a thickness of 9 μm. After standing and drying, the pretreated steel core is obtained. The hard aluminum wire is divided into two layers of 12 inner strands and 14 outer strands and wound on the outer layer of the pretreated steel core. Then, it is immersed in a 10wt% sodium hydroxide solution for 6 min. After washing and drying, the anti-corrosion coating of 13 μm thickness is sprayed again. After drying, the steel core aluminum stranded wire is obtained.
[0032] This embodiment also provides a steel-cored aluminum stranded wire prepared by the above method.
[0033] Example 2 Example 2 provides a method for preparing corrosion-resistant steel-cored aluminum stranded wire, comprising the following steps: (1) Weigh out 0.15 wt% silver-plated graphene and 99.85 wt% aluminum alloy, ball mill and mix the aluminum alloy with the silver-plated graphene of Preparation Example 7, heat to 710-720 ℃ to melt, then refine and dehydrogenate, continuously cast and extrude at 680 ℃ to obtain round aluminum rods, and then draw to obtain hard aluminum wires; (2) After the steel core is degreased, washed and dried, and sandblasted to remove rust, the anti-corrosion coating of Preparation Example 2 is sprayed on the surface of the steel core with a thickness of 9 μm. After standing and drying, the pretreated steel core is obtained. The hard aluminum wire is divided into two layers of 12 inner strands and 14 outer strands and wound on the outer layer of the pretreated steel core. Then, it is immersed in a 10wt% sodium hydroxide solution for 5 min, washed and dried, and then sprayed with a 13 μm thick anti-corrosion coating again. After drying, the steel core aluminum stranded wire is obtained.
[0034] This embodiment also provides a steel-cored aluminum stranded wire prepared by the above method.
[0035] Example 3 Example 3 provides a method for preparing corrosion-resistant steel-cored aluminum stranded wire, comprising the following steps: (1) Weigh out 0.30 wt% silver-plated graphene and 99.7 wt% aluminum alloy, ball mill and mix the aluminum alloy with the silver-plated graphene of Preparation Example 8, heat to 710-720 °C to melt into aluminum liquid, refine and dehydrogenate, continuously cast and extrude at 690 °C to obtain round aluminum rods, and then draw to obtain hard aluminum wires; (2) After the steel core is degreased, washed and dried, and sandblasted to remove rust, the anti-corrosion coating of Preparation Example 3 is sprayed on the surface of the steel core with a thickness of 9 μm. After standing and drying, the pretreated steel core is obtained. The hard aluminum wire is divided into two layers of 12 inner strands and 14 outer strands and wound on the outer layer of the pretreated steel core. Then, it is immersed in a 10wt% sodium hydroxide solution for 7 min. After washing and drying, a 13 μm thick anti-corrosion coating is sprayed again. After drying, the steel core aluminum stranded wire is obtained.
[0036] This embodiment also provides a steel-cored aluminum stranded wire prepared by the above method.
[0037] (III) Comparative Example Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the anti-corrosion coating in step (2) is replaced with the coating of Preparation Example 4.
[0038] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that the anti-corrosion coating in step (2) is replaced with the coating of Preparation Example 5.
[0039] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the silver-plated graphene in step (1) is replaced with graphene.
[0040] (iv) Test Examples The hard aluminum wire and steel-cored aluminum stranded wire prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests.
[0041] Conductivity test: The conductivity of the hard aluminum wires in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 3048.2-2007 "Test methods for electrical properties of wires and cables - Part 2: Test for resistivity of metallic materials". The results are shown in Table 1.
[0042] Tensile strength test: The tensile strength of the hard aluminum wires in Examples 1-3 and Comparative Examples 1-3 was tested in accordance with GB / T 4909.3-2009 "Test methods for bare wires - Part 3: Tensile test". The results are shown in Table 1.
[0043] Corrosion resistance test: The aluminum stranded wires of Examples 1-3 and Comparative Examples 1-3 were tested according to the neutral salt spray test standard in GB / T 10125-2021 "Civilization Tests in Artificial Atmospheres - Salt Spray Tests" for a test period of 480 hours. The tensile strength before and after corrosion was measured according to the tensile strength determination method, and the tensile strength retention rate was calculated. The results are shown in Table 1.
[0044] Table 1. Test data on conductivity and tensile strength of hard aluminum wire and corrosion resistance of steel-cored aluminum stranded wire. As shown in Table 1, the hard aluminum wires prepared in Examples 1-3 of the present invention have both high conductivity and tensile strength, and the steel-cored aluminum stranded wires prepared have good corrosion resistance.
[0045] Compared to Example 1, Comparative Example 1 omitted the anti-corrosion filler in the anti-corrosion coating, resulting in a significant decrease in anti-corrosion performance. This indicates that adding anti-corrosion filler helps improve the anti-corrosion performance of aluminum stranded wire. This is because high-entropy borides have high hardness and high chemical stability, and as fillers, they can effectively improve the wear resistance and anti-corrosion performance of the wire. Comparative Example 2 replaced the anti-corrosion filler with unmodified high-entropy borides. Although its anti-corrosion performance was better than that of Comparative Example 1, it was still lower than that of Example 1. This shows that the present invention further improves the anti-corrosion effect by modifying the high-entropy borides. Specifically, the modified anti-corrosion filler grafted thiol groups and trifluoromethyl groups onto the surface of the borides. The thiol groups can form a cross-linked network with epoxy resin, improving the compatibility of the filler with the organic matrix, while the trifluoromethyl groups impart excellent chemical stability to the coating. The two construct an organic-inorganic composite network structure, thereby significantly improving the corrosion resistance of the aluminum stranded wire.
[0046] Compared to Example 1, Comparative Example 3, which replaced silver-plated graphene with graphene, showed a significant decrease in the tensile strength and conductivity of the duralumin wire. This indicates that the addition of silver-plated graphene can simultaneously improve the tensile strength and conductivity of the duralumin wire. The mechanism of action is as follows: silver-plated graphene combines the high conductivity of both silver and graphene, forming a good conductive path in the alloy matrix, thereby improving conductivity; simultaneously, graphene, as a reinforcing phase, can refine grains and hinder dislocation movement, improving the mechanical properties of the matrix; and the surface silver plating treatment improves the dispersion and wettability of graphene in the aluminum alloy matrix, further enhancing its reinforcing effect.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. Based on the present invention, some modifications or substitutions can be made, but these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of protection claimed by the present invention.
Claims
1. A method for preparing corrosion-resistant steel-cored aluminum stranded wire, characterized in that, Includes the following steps: (1) Aluminum alloy and silver-plated graphene are mixed evenly, melted and then refined and dehydrogenated, and then continuously cast and extruded and drawn to obtain hard aluminum wire. (2) Spray anti-corrosion coating on the surface of the steel core and dry it to obtain a pretreated steel core; strand hard aluminum wire into the outer layer of the pretreated steel core, immerse it in alkaline solution, clean it, dry it, spray anti-corrosion coating again and dry it to obtain steel core aluminum stranded wire. The anti-corrosion coating is composed of the following components by weight percentage: 15-24 wt% anti-corrosion filler, 4-8 wt% butyl acetate, 22-27 wt% polyvinyl fluoride resin, and the balance being epoxy resin.
2. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 1, characterized in that, The corrosion-resistant filler is prepared by the following process: (a) A mixture of metal oxide, boron carbide and graphite was calcined in an inert gas atmosphere to obtain a high-entropy boride; (b) The high-entropy boride was ultrasonically treated in an acid solution, and then heated and stirred with a silane coupling agent in ethanol to obtain the modified high-entropy boride; (c) Modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid and dehydrating agent are added to toluene and stirred under heating conditions to obtain corrosion-resistant filler.
3. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 2, characterized in that, The metal oxide in step (a) is composed of any five raw materials in an equimolar ratio selected from HfO2, ZrO2, Ta2O5, V2O5, Nb2O5, TiO2, Cr2O3, MoO3, WO3, or CeO2; the molar ratio of the metal oxide, boron carbide, and graphite is 1:(0.7-1.1):(0.3-0.5); the calcination temperature is 1500-1600 ℃, and the time is 2-4 h.
4. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 2, characterized in that, The ultrasonic treatment in step (b) involves soaking in a 3-5 wt% nitric acid solution for 0.5-1.5 h; the silane coupling agent is KH550; the ratio of the high-entropy boride, silane coupling agent, and ethanol is 100 g: (10-15) g: (300-400) mL; the heating and stirring temperature is 50-70 ℃, and the time is 1-2 h.
5. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 2, characterized in that, The dehydrating agent in step (c) is propylphosphonic anhydride; the ratio of the modified high-entropy boride, mercaptoacetic acid, trifluoropropionic acid, dehydrating agent and toluene is 100 g: (2-3) g: (3-4.5) g: (10-15) g: (200-250) mL; the heating temperature is 40-50 ℃, and the stirring reaction time is 2-5 h.
6. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 1, characterized in that, The silver-plated graphene described in step (1) is prepared by the following method: Pretreated graphene is dispersed in a chemical plating solution, sonicated for 20-40 min, filtered, and washed to obtain silver-plated graphene. The chemical plating solution is composed of the following raw materials by mass percentage: 2wt% silver nitrate, 2-3wt% glucose, 6-10wt% potassium sodium tartrate, 4-5wt% ethanol, and the balance is water.
7. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 6, characterized in that, The pretreated graphene is obtained by heating and soaking graphene in a sodium hydroxide solution; the ratio of the pretreated graphene to the chemical plating solution is 1 g: (125-250) mL.
8. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 1, characterized in that, The mass ratio of silver-plated graphene to aluminum alloy in step (1) is (0.15-0.3):(99.85-99.7); the temperature during continuous casting and extrusion is 680-690 ℃.
9. The method for preparing corrosion-resistant steel-cored aluminum stranded wire according to claim 1, characterized in that, The aluminum alloy described in step (1) is composed of the following components by mass percentage: Fe 0.11-0.21 wt%, Si 0.15-0.24 wt%, B 0.06-0.18 wt%, Cu 0.25-0.32 wt%, La 0.04-0.08 wt%, Ce 0.06-0.12 wt%, with the balance being Al.
10. Corrosion-resistant steel-cored aluminum stranded wire prepared by the preparation method according to any one of claims 1-9.